2018
DOI: 10.1007/s15010-018-1168-7
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous acute hepatitis E: treatment with sofosbuvir and ribavirin

Abstract: In conclusion, although more data are required before firm conclusions could be drawn, the combination of sofosbuvir and ribavirin in not immunosuppressed patients with acute hepatitis E may be able to clear HEV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…In both these studies where sofosbuvir had no effect on G1 HEV, the Sar55/S17/luc replicon, which harbors an insertion from the human ribosomal S17 protein within the hypervariable region, was utilized (37,62). This S17 insertion dramatically enhances replication levels (37) and, as such, likely renders it less susceptible to sofosbuvir inhibition than wildtype viruses and other replicons which lack this insertion, as previously observed with G1634R-associated ribavirin failure (63,64).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In both these studies where sofosbuvir had no effect on G1 HEV, the Sar55/S17/luc replicon, which harbors an insertion from the human ribosomal S17 protein within the hypervariable region, was utilized (37,62). This S17 insertion dramatically enhances replication levels (37) and, as such, likely renders it less susceptible to sofosbuvir inhibition than wildtype viruses and other replicons which lack this insertion, as previously observed with G1634R-associated ribavirin failure (63,64).…”
Section: Discussionmentioning
confidence: 61%
“…Clinically, sofosbuvir has been used in a few individual cases with or without ribavirin to treat HEV G3-infected patients with variable success (63,(65)(66)(67)(68), ranging from a reduction of HEV RNA to undetectable levels (63,66) to treatment failure or relapse following treatment (65,67,68). These mixed reports of efficacy have raised questions around the pursuit of sofosbuvir as an HEV antiviral (69), indicating that further work is required to ascertain its suitability as an anti-HEV therapeutic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sofosbuvir was shown to inhibit HEV Kernow-C1 replication in vitro and the combination with ribavirin even resulted in an additive effect [48]. However, there is not enough clinical data yet to estimate the effectivity in vivo due to few contradictory reports [49,50,51]. Recent reports suggest silvestrol as a drug candidate to treat HEV [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was administered as combination therapy with ribavirin in some ribavirin-resistant cases. Biliotti et al[ 137 ] showed the clearance of the HEV with sofosbuvir/ribavirin combination therapy in patients with acute HEV infection. In another study, combination therapy was reported to treat refractory HEV infection in an immunosuppressed individual[ 138 ].…”
Section: Promising Treatment Options For Ribavirin-resistant Hev Infementioning
confidence: 99%